1988
DOI: 10.1007/bf00271585
|View full text |Cite
|
Sign up to set email alerts
|

Application of prazosin is associated with an increase of insulin sensitivity in obese patients with hypertension

Abstract: The aim of this study was to determine whether insulin sensitivity measured by the euglycaemic insulin clamp technique is lower in patients with primary hypertension than in matched healthy control subjects, and whether this sensitivity was affected after 12 weeks of antihypertensive treatment with the alpha 1-adrenoceptor blocking drug prazosin. Twelve moderately obese normoglycaemic patients (four men), with hypertension not previously treated with pharmacological agents and diastolic blood pressure above 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
112
1
3

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(120 citation statements)
references
References 35 publications
3
112
1
3
Order By: Relevance
“…They indicated that the a1-blockers inhibit Ca2+ mobilization in platelets and that this mechanism may be the means by which a1-blockers inhibit platelet aggregation. The a1-blocker is reported to improve insulin sensitivity (18) and lipid metabolism (19) in patients with essential hypertension. The mechanisms underlying these effects may be explained by the a1-blocker's catecholamine blocking effects and vasodilator effects (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They indicated that the a1-blockers inhibit Ca2+ mobilization in platelets and that this mechanism may be the means by which a1-blockers inhibit platelet aggregation. The a1-blocker is reported to improve insulin sensitivity (18) and lipid metabolism (19) in patients with essential hypertension. The mechanisms underlying these effects may be explained by the a1-blocker's catecholamine blocking effects and vasodilator effects (18).…”
Section: Discussionmentioning
confidence: 99%
“…The a1-blocker is reported to improve insulin sensitivity (18) and lipid metabolism (19) in patients with essential hypertension. The mechanisms underlying these effects may be explained by the a1-blocker's catecholamine blocking effects and vasodilator effects (18). Although the exact mechanisms of our observation and those of others indicating the inhibitory effect of an a-blocker on platelet function remain to be clarified, it appears that the a-blocker's effect on platelets, insulin sensitivity, and lipid metabolism may be beneficial in preventing hypertensive end organ damage.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of glucose infused during the last 60 min after a steady-state was achieved was calculated (M) and was related to the mean insulin concentration for the estimation of insulin sensitivity (M/I) (16,18). Both M and M/I are estimations of the total peripheral insulin sensitivity regarding the glucose metabolism, based on the assumption that the hyperinsulinaemic level totally inhibits glucose production from the liver (19).…”
Section: Evaluation Of Insulin Sensitivitymentioning
confidence: 99%
“…Insulin resistance not only occurs in manifest Type 2 diabetes, but also in impaired glucose tolerance, obesity, essential hypertension and even in 25% of subjects with normal glucose tolerance [9], i.e. in a variety of "pre-diabetic states".…”
Section: Letters To the Editormentioning
confidence: 99%
“…Improvement of insulin sensitivity has been suggested not only for ACE inhibitors but also for prazosin [9], metoprolol [10] and atenolol [10]. However, these were placebo controlled trials and a non-specific effect of blood pressure reduction independent of the antihypertensive drug used has not been excluded.…”
Section: Letters To the Editormentioning
confidence: 99%